Edukasi Kesehatan tentang Penyakit Degeneratif dan Informasi Obat di Kampung Biru, Banjarmasin, Indonesia: Health Education on Degenerative Diseases and Medication Information in Kampung Biru, Banjarmasin, Indonesia - Jihan, Jihan; Wahyuni, Arifah Sri; Rizakh, Faizah Siti; Lathif, Elmasrini; Safitri, Dewi; Amelia, Ratih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Degenerative diseases such as hypertension, diabetes mellitus, and hypercholesterolemia are major global health concerns with high prevalence in Indonesia, including in Kampung Biru, Banjarmasin. This community service initiative aimed to enhance public knowledge about the prevention and management of degenerative diseases, while also providing medication information through the Drug Information Service (DIS). The program involved 58 participants who underwent health screenings (blood pressure, blood glucose, cholesterol, and uric acid levels), disease-specific group education, and DIS sessions conducted by pharmacists. Results showed a 60.34% improvement in participants' knowledge, with a 98.27% satisfaction rate. Data analysis revealed a higher prevalence of these diseases among the elderly (aged 45 years and above), aligning with national epidemiological trends. The program demonstrated the effectiveness of a collaborative approach involving academics, healthcare professionals, and the community in promoting health literacy and preventive care.